2014
DOI: 10.1111/een.12140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvester ants of the genus Pogonomyrmex on the soil seed bank around their nests in the central Monte desert, Argentina

Abstract: 1. The abundance and composition of soil seed banks is a key determinant of plant community structure. Harvester ants can remove huge quantities of preferred seeds close to the nest affecting composition and spatial distribution of plants.2. In the central Monte desert (Argentina) ants of the genus Pogonomyrmex have high seed removal rates, especially of the five main grasses. The aim of this study was to establish if their foraging activity affects spatial patterns of the soil seed bank around their nests. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The diversity and density of seed banks in sites near ant nests were higher than those of control sites, which is consistent with other studies (Leal et al, 2007;Inés et al, 2014). Some studies indicated that the negative impacts of ants on seed bank in desert areas are related to foraging behavior and seed consumption of ants (Costa et al, 2008;Pirk and de Casenave, 2014).…”
Section: Ants Seedling Establishment and Seed Banksupporting
confidence: 90%
“…The diversity and density of seed banks in sites near ant nests were higher than those of control sites, which is consistent with other studies (Leal et al, 2007;Inés et al, 2014). Some studies indicated that the negative impacts of ants on seed bank in desert areas are related to foraging behavior and seed consumption of ants (Costa et al, 2008;Pirk and de Casenave, 2014).…”
Section: Ants Seedling Establishment and Seed Banksupporting
confidence: 90%
“…Several works highlight the negative impacts of ants on plants in desert areas (Brown, Reichman & Davidson ; Costa et al . ; Pirk & Lopez De Casenave ). We complement these findings highlighting the positive influence of ants that inhabit desert lands on soil fertility and vegetation performance.…”
Section: Discussionmentioning
confidence: 98%
“…However, the case for ants is unclear. Ants of the genus Pogonomyrmex modify the seed bank (Taber, 1998; MacMahon et al., 2000; Pirk & Lopez De Casenave, 2014; Luna et al., 2018), which eventually could change the plant community. In fact, these ants increase the diversity of small‐seeded plants in the Sonoran Desert, but the underlying mechanisms behind these changes are unclear (Samson et al., 1992).…”
Section: Introductionmentioning
confidence: 99%